Management of diaphragmatic hernia in cats: A review of four cases - Varghese, Reji; Philip, Laiju M.; Jos B.M., Nijin; P., Jishi Das; Prakash, Amal; Raut, Shubham W.; B., Rahul; Sanjaykumar, Udharwar; Venugopal, Syam K.; S., Anoop; Martin, K.D. John (Indian Journal of Veterinary Surgery, 2026)
-